PERBANDINGAN KUASA UJI PENDEKATAN BIGGERS DAN SATTERTHWAITE-COCHRAN DALAM MENGANALISIS DATA HILANG PADA RANCANGAN KELOMPOK TERACAK LENGKAP - Achmad Firdaus; Mustofa Usman; Netti Herawati (FORUM STATISTIKA DAN KOMPUTASI, 2003)
This study was aimed to compare type I error in estimating missing data by Biggers and Satterhwaite-Cochran methods in Randomized Comple Block Design. Simulation study using Gauss software showed that type I error for Biggers approach are over estimate. The problem can be overcomed by Satterhwaite-Cochran approach.Keyword: Missing data, randomized Block design, Biggers, Satterhwaite-Cochran.